EFFECTS OF SOIL TILLAGE AND SOWING TECHNOLOGIES ON WINTER WHEAT (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2001)
The influence of soil tillage and sowing technologies on the yield of winter wheat were studied on sod podzolic loam soils in the LUA Research and Study Farm “Vecauce” during 1998 to 2000. Classic early ploughing, late ploughing with soil pacomat and sowing without soil reversing were used as comparison variants o f soil tillage for winter wheat. The using of soil pacomat and local mineral fertilizing increased the yield o f winter wheat in the research conditions. Direct sowing and conservation soil tillage gave a decrease o f grain cost and provide the same level o f yield achieved with classic soil tillage and sowing technologies.